2020
DOI: 10.1128/iai.00948-19
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Deficiency Exacerbates Trypanosoma cruzi Infection

Abstract: Chagas disease, caused by the intracellular protozoan parasite Trypanosoma cruzi, is a public health problem affecting 6 to 8 million people, mainly in Latin America. The role of microRNAs in the pathogenesis of Chagas disease has not been well described. Here, we investigate the role of microRNA-155 (miR-155), a proinflammatory host innate immune regulator responsible for T helper type 1 and type 17 (Th1 and Th17) development and macrophage responses during T. cruzi infection. For this, we compared the surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
2
20
0
2
Order By: Relevance
“…Our studies have shown decreased accumulation of Ly6C + in ammatory monocytes and DCs in miR155KO mice, associated with a signi cantly increased parasite load and with the reduced expression of those proin ammatory mediators. However, it is contradictory that aberrant miR-155 expression has recently been shown to adversely affect Ly6C + in ammatory monocytes migration in L. donovani and T. cruzi, which is due to a fact that in ammatory monocytes facilitate the growth of the parasites in the spleen in visceral leishmaniasis and trypanosomosis [16,17]. These results demonstrate that miR155 de ciency exacerbated T. gondii infection through the down-regulation of DCs and in ammatory monocyte in ltration.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Our studies have shown decreased accumulation of Ly6C + in ammatory monocytes and DCs in miR155KO mice, associated with a signi cantly increased parasite load and with the reduced expression of those proin ammatory mediators. However, it is contradictory that aberrant miR-155 expression has recently been shown to adversely affect Ly6C + in ammatory monocytes migration in L. donovani and T. cruzi, which is due to a fact that in ammatory monocytes facilitate the growth of the parasites in the spleen in visceral leishmaniasis and trypanosomosis [16,17]. These results demonstrate that miR155 de ciency exacerbated T. gondii infection through the down-regulation of DCs and in ammatory monocyte in ltration.…”
Section: Discussionmentioning
confidence: 90%
“…As miR-155 has been shown to be critical for regulating T cell responses as well as in ammatory responses and cytokine signals, which have the well-documented roles in the control of intracellular pathogens, including T. cruzi and Leishmania donovani [16,17], we further analyzed the production of cytokines Th1-associated IFN-γ, IL-2, Th2-associated IL-4 and IL-13, Th17-associated IL-17A and IL-17F by splenic cells harvested from WT and miR155KO (miR-155 −/− ) mice after infection with T. gonii PRU cysts.…”
Section: Results Mir155 De Ciency Enhanced the Susceptibility To T Gmentioning
confidence: 99%
See 3 more Smart Citations